Analysis of risk factors for non-alcoholic fatty liver disease in hospitalized children with obesity before the late puberty stage - Zhou, Lishan; Zhang, Linli; Zhang, Lingling; Yi, Wei; Yu, Xue; Mei, Hong; Xiao, Haiyan; Wang, Yuji; Qin, Huan; Xiong, Xiaoli; Yan, Suqi; Dong, Hui; et al. (Frontiers in Endocrinology, 2023)
Objective: This study aimed to determine the clinical characteristics of obese pediatric nonalcoholic fatty liver disease (NAFLD) in central China and verify the applicability of some known risk factors for pediatric NAFLD before late puberty.: This was a retrospective case-control study. A total of 1029 inpatients at Wuhan Children's Hospital before the late puberty stage were enrolled in the study, including 815 children with obesity (non-NAFLD group) and 214 children with obesity and NAFLD (NAFLD group) diagnosed by liver ultrasound. Subgroup analyses were performed according to sex and puberty. The anthropometric indices and laboratory test data of these 1029 children were sorted. After intergroup comparison, a logistic regression model was used to determine the risk factors for pediatric NAFLD.Significant risk factors for NAFLD were further tested using receiver operating characteristic (ROC) curves to evaluate their ability to predict an early diagnosis of NAFLD.